The Effect of Motivating Operations on Equivalence-Based Instruction Outcomes. - Brodsky, Julia; Fienup, Daniel M.; Lanson, Robert N.; Marin, Ramon (Psychological Record, 2024)
This study examined the role of meaningfulness and motivating operations on the outcomes for equivalence-based instructions (EBI). In Experiment 1, we compared the establishment of two equivalence classes; both classes were considered as meaningful (Chemistry and Developmental Psychology contents) but only Developmental Psychology was expected to be educationally relevant to General Psychology students. Participants were assigned to two groups, in which only one content was presented. In Experiment 1, participants in the Chemistry group showed better performances compared to the Developmental Psychology group. This result suggests that, under similar conditions, equivalence classes on Chemistry contents were easier to learn. Experiment 2 assessed the effects of motivating operations in establishing equivalence classes. We systematically included instructions on whether participants would learn relations between meaningful stimuli and whether they were educationally beneficial. New participants were assigned to three groups. In the Abstract condition participants were told the stimuli were not meaningful and not educationally beneficial. The two meaningful conditions were the same as Experiment 1, with the Developmental Psychology classes being directly relevant to the course from which participants were recruited. The outcomes indicated that meaningful stimuli facilitated equivalence class formation and direct educational relevance further enhanced outcomes. These findings provide preliminary evidence of the role of motivating operations in enhancing equivalence class formation and relational frame theory's concept of ROE-M.